Desain Balanced Scorecard Untuk Mencapai Target Strategis PDAM Hulu Sungai Utara, Kalimantan Selatan - Clara Rasida; Hendrawan Santosa Putra; Oktaviani Ari Wardhaningrum (Fakultas Ekonomi Universitas Andalas, 2021)
A company needs to measure its financial and non-financial aspects to prove its proper performance. Balanced Scorecard is one of the tools to measure performance both in financial and non-financial. This study aims to implement Balanced Scorecard design that is in line with the vision and strategy of PDAM Hulu Sungai Utara to achieve the desired performance targets. This is descriptive qualitative research. The data collection methods used were interview, documentation, and observation methods. The type of data used is both primary data in the form of interviews, and secondary data in the form of financial reports and other data attachments. The data analysis method in this study begins by presenting an overview of the next PDAM HSU, classifying the strategic plans that are applied, explaining the causal relationship between strategic plans, determining indicators and targets in each perspective, and describing the Balanced Scorecard design. The results of this study are the measurements in accordance with strategic objectives in each perspective according to the Balanced Scorecard concept. It is expected to make PDAM HSU easier for achieving its strategic goals.